MAPAC: Process Analysis for Citizen Approach Method - Pires, Emmanuel; Araújo, Renata (iSys - Journal of Information Systems, 2020)
The use of Information and Communication Technologies has been understood as an important mean for public organizations to provide quality services to citizens, reducing the gap among public administration and its clients. This paper describes the Process Analysis for Citizen Approach Method (MAPAC), which aims to guide a process analyst to identify and propose solutions in order to reduce the gap between citizens and the public process. Two studies were carried out to evaluate MAPAC, one at the National Cancer Institute (INCA) in Brazil and another at a specialized unit in conflict mediation at the Rio de Janeiro Court of Justice (TJRJ). The results have describe the method potential to support the identification of alternatives of citizen participation.